Optimizing Access to Financial Capital of Creative Economy for Startups Towards Global Competitiveness - Sugeng Santoso (Bina Nusantara University, 2020)
The lack of understanding of the financial capital of the creative economy regarding non-bank financial institutions limits the growth of Indonesia’s creative economy. Strategies through policies, capital owners, creative economy players and bring together capital owners with players. The capital of the creative economy is represented on the criteria: entrepreneurial characteristics, product/service characteristics, market characteristics, and financial characteristics. The method used is a qualitative analysis and quantitative analysis which starts from data collection, data analysis, participatory discussion, drawing conclusions, formulating policies and stakeholder synergy. The startup mentoring scoring instrument is a framework for investor’s decision making to invest in the startup. 3 scoring elements of mentoring startup scoring: Product & key person with a weight of 55%, Traction with a weight of 25%, and Investment with a weight of 20%. Primary data were obtained by participatory observation, field studies, and key informant interviews through startup mentoring programs, workshops, and startup competitions. Results: Among 20% of startups pitched in front of investors, there are 11% of startups that investors interested in and got funding from a consortium of Indonesian and foreign venture capital companies. Matchmaking activities increase added value, and the implemented policy also increases added value.